2017
DOI: 10.3390/nu9040369
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Different Water-Soluble Choline Compounds Differ between Human Preterm and Donor Milk

Abstract: Choline is essential for infant development. Human milk choline is predominately present in three water-soluble choline (WSC) forms: free choline (FC), phosphocholine (PhosC), and glycerophosphocholine (GPC). It is unclear whether mother’s own preterm milk and pooled donor milk differ in WSC composition and whether WSC compounds are interrelated. Mother’s own preterm milk (n = 75) and donor milk (n = 30) samples from the neonatal intensive care unit, BC Women’s Hospital were analyzed for WSC composition using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…In regards to the variability of water-soluble forms of choline concentration in expressed human milk, we observed diurnal changes in milk FC and GPC concentrations, but not in PhosC and total water-soluble choline forms. The total concentration of water-soluble forms of choline in expressed human milk we found was similar to the concentrations previously reported by our team for Canadian lactating women [24,32] and by Fischer et al for US women [11]. Because no substantial diurnal changes were observed and the total concentration of water-soluble forms of choline in human milk seems stable, we conclude that the time point of milk sample collection in studies on water-soluble forms of choline may not influence the study outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In regards to the variability of water-soluble forms of choline concentration in expressed human milk, we observed diurnal changes in milk FC and GPC concentrations, but not in PhosC and total water-soluble choline forms. The total concentration of water-soluble forms of choline in expressed human milk we found was similar to the concentrations previously reported by our team for Canadian lactating women [24,32] and by Fischer et al for US women [11]. Because no substantial diurnal changes were observed and the total concentration of water-soluble forms of choline in human milk seems stable, we conclude that the time point of milk sample collection in studies on water-soluble forms of choline may not influence the study outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, for this preliminary study, we were mainly focusing on the comparison of choline concentrations between before and after pasteurization. We acknowledge that the long-term storage at −80 • C may have affected the milk concentrations of the water-soluble forms of choline; however, the total water-soluble choline concentration in the pre-pasteurized samples was similar to that of the fresh milk samples in the stability study (1241 µmol/L versus 1231 µmol/L, respectively), as well as compared to those reported in the literature [11,24,32]. This seems to reflect that the total water-soluble choline concentration was not affected by the long-term storage at −80 • C and that our findings may contribute to the literature of how human milk is altered by pasteurization.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…At this time, the potential consequences of altering the forms of choline in the offspring’s diet, such as reducing the proportion of choline from phosphocholine, are unknown. Previous studies [ 11 , 26 ] that have observed differences in choline forms have proposed that future studies should address the role of the difference forms of choline in the maternal and offspring diet, and the implications on offspring health.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence exists regarding the protective effects of MOM in reducing the risk of necrotizing enterocolitis (NEC), late-onset sepsis (LOS), and retinopathy of prematurity (ROP) in VLBW infants, questions remain regarding whether DHM provides the same benefits [5,[8][9][10][11][12][13][14]. Numerous MOM components which could contribute to protect against adverse outcomes of prematurity are reduced or absent in DHM which is usually pasteurized [14][15][16].…”
Section: Introductionmentioning
confidence: 99%